Donald Trump, the Role of the Latino Electorate and Latino Republicans in the 2020 Presidential Elections: Lessons for the 2024 Presidential Elections - Anna Bartnik (Politeja)
Latino political participation is attracting growing attention due to the size of the population of Hispanic origin. Once portrayed as a sleeping giant, today they dispute such and other mistaken narratives. The article argues the popular belief that Hispanics are unlikely to support Republicans and seeks for determinants that shape Latino political support. The analysis offers an indepth query into Donald Trump’s anti-immigration policy that affected the Hispanic population living in the US, and explores the issue of Latino support for a Republican candidate in the 2020 and 2024 presidential elections. It also argues that Trump’s hard stance on immigrants was not significant enough to convert Hispanic Republican voters to Democrats.